Diagonal and off-diagonal susceptibilities of conserved quantities in relativistic heavy-ion collisions. (26th October 2016) - Chatterjee, Arghya; Chatterjee, Sandeep; Nayak, Tapan K; Sahoo, Nihar Ranjan
Abstract: Susceptibilities of conserved quantities, such as baryon number, strangeness and electric charge are sensitive to the onset of quantum chromodynamics phase transition, and are expected to provide information on the matter produced in heavy-ion collision experiments. A comprehensive study of the second order diagonal susceptibilities and cross correlations has been made within a thermal model approach of the hadron resonance gas model as well as with a hadronic transport model, ultra-relativistic quantum molecular dynamics. We perform a detailed analysis of the effect of detector acceptances and choice of particle species in the experimental measurements of the susceptibilities for heavy-ion collisions corresponding to s NN  = 4 GeV to 200 GeV. The transverse momentum cutoff dependence of suitably normalised susceptibilities are proposed as useful observables to probe the properties of the medium at freezeout.